Research of Surface Wear Resistance of Aluminum Alloy Modified with Minerals using Sclerometry Method - A. V. Skazochkin; G. G. Bondarenko; P. Żukowski (Приборы и методы измерений, 2019)
Improving the wear resistance of the surface of metal parts used in various industries is one of the relevant areas of materials science. The aim of this work was a comparative study of the wear resistance of a sample of an aluminum alloy (EN AW-2024, an aluminum alloy of the Al-Cu-Mg system) modified with ultrafine particles of minerals using the sclerometry method, which makes it possible to measure the physicomechanical properties of the material at the microscale, as well as determining some tribological parameters (hardness and elastic modulus) of a duralumin sample with a mineral coating.Wear resistance was measured using a NanoScan-4D scanning hardness tester using the multi-cycle friction method using a sapphire sphere with control of the pressing force and the deepening of the tip into the sample. The use of such a measurement system is especially important when testing thin modified layers, when the layer thickness is comparable with the surface roughness parameters and the influence of the substrate is excluded.The measurement results showed that the wear resistance of the surface of an aluminum alloy sample modified with ultrafine mineral particles increased by more than 12 times compared to the wear resistance of an aluminum alloy surface without modification. Also, measurements of the hardness and elastic modulus of the surface of the modified sample were performed taking into account the features of measuring the mechanical parameters of thin layers.The obtained parameters of the modified surface of the aluminum alloy can be further used to build models of the processes of friction and wear of the surface modified by ultrafine particles of minerals. The lack of an acceptable explanation of the nature of the special properties of the surface modified by particles of minerals of natural origin does not exclude the use of the observed effects to significantly increase the resource of various parts and mechanisms.